2013
DOI: 10.1080/13668803.2012.675744
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' integration of work, home and community in master planned communities: what's different?

Abstract: Work/life research needs to incorporate consideration of community issues and is rarely conducted in master planned communities (MPCs). To address this gap the present exploratory study aimed to examine the specific work/life integration (WLI) experiences of working mothers residing in an Australian MPC. Fifteen interviews were conducted with 10 working mothers. Data analysis involved thematic coding of interview transcripts. Findings showed that working mothers in the present study had difficulties, similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Consistent with other literature on MPCs, when asked about why they chose to buy a house in Eucalypt Hill the main reason participants gave was affordability (Dowling et al, 2010;Vujinović et al, 2013;Warr & Robson, 2013). Generally speaking, the purchase price of a detached house or semi-detached town house in an MPC is almost half that of a similar size in inner Melbourne.…”
Section: Buying Into Communitymentioning
confidence: 58%
See 3 more Smart Citations
“…Consistent with other literature on MPCs, when asked about why they chose to buy a house in Eucalypt Hill the main reason participants gave was affordability (Dowling et al, 2010;Vujinović et al, 2013;Warr & Robson, 2013). Generally speaking, the purchase price of a detached house or semi-detached town house in an MPC is almost half that of a similar size in inner Melbourne.…”
Section: Buying Into Communitymentioning
confidence: 58%
“…In the absence of community place-based ties are appealing because they are more tangible and therefore perceived as more readily able to be acted upon, designed and controlled (Talen, 1999). Some research has found that positive results can arise from such arrangements, including increased interactions between residents, a sense of belonging and overall satisfaction (Goodman & Douglas, 2010;Vujinović et al, 2013). Although constructive, these outcomes have been described as creating a "sense of community" rather than representing a genuine community in its own right (Talen, 1999;Walters & Rosenblatt, 2008;Warr & Robson, 2013).…”
Section: Creating Place-based Communitiesmentioning
confidence: 93%
See 2 more Smart Citations